The laboratory diagnosis and follow up of strongyloidiasis: a systematic review. - Ana Requena-Méndez; Peter Chiodini; Zeno Bisoffi; Dora Buonfrate; Eduardo Gotuzzo; José Muñoz (PLoS Neglected Tropical Diseases, 2013)
Background Strongyloidiasis is frequently under diagnosed since many infections remain asymptomatic and conventional diagnostic tests based on parasitological examination are not sufficiently sensitive. Serology is useful but is still only available in reference laboratories. The need for improved diagnostic tests in terms of sensitivity and specificity is clear, particularly in immunocompromised patients or candidates to immunosuppressive treatments. This review aims to evaluate both conventional and novel techniques for the diagnosis of strongyloidiasis as well as available cure markers for this parasitic infection. Methodology/principal findings The search strategy was based on the data-base sources MEDLINE, Cochrane Library Register for systematic review, EmBase, Global Health and LILACS and was limited in the search string to articles published from 1960 to August 2012 and to English, Spanish, French, Portuguese and German languages. Case reports, case series and animal studies were excluded. 2003 potentially relevant citations were selected for retrieval, of which 1649 were selected for review of the abstract. 143 were eligible for final inclusion. Conclusions Sensitivity of microscopic-based techniques is not good enough, particularly in chronic infections. Furthermore, techniques such as Baermann or agar plate culture are cumbersome and time-consuming and several specimens should be collected on different days to improve the detection rate. Serology is a useful tool but it might overestimate the prevalence of disease due to cross-reactivity with other nematode infections and its difficulty distinguishing recent from past (and cured) infections. To evaluate treatment efficacy is still a major concern because direct parasitological methods might overestimate it and the serology has not yet been well evaluated; even if there is a decline in antibody titres after treatment, it is slow and it needs to be done at 6 to 12 months after treatment which can cause a substantial loss to follow-up in a clinical trial.